Critical Factors for the Successful Implementation of a Strategic Business Plan among Small and Medium Size Enterprises - Paul Saah (International Review of Management and Marketing, 2022)
In today's dynamic and competitive business world, small and medium-sized enterprises require strategic planning as a business tool. The purpose of this study was to determine requirements that a small business must meet to successfully implement a strategic business plan. The study employs a qualitative research approach for collecting and analysing data. A non-probability sampling method was used to select the 20 small business owners and managers who participated in the study. The data collection was done through the conduction of interviews and thematic analysis was carry out to analyse the data. The findings demonstrate that strategic business planning helps small businesses in analysing their existing contexts, examining how current trends could affect them, and determining best practices to overcome potential barriers to success. The study equally portrays those small businesses that implement strategic business planning into their operations have a higher chance of success than those that do not.